Spiritualitas Yesus Kristus Sebagai Prinsip Dasar Kehidupan Kristiani Masa Kini Menurut Teks Filipi 2:1-11 - Lake, Ignasius; Pagang, Maria Yulia; Inya, Fridolin Tamo; Muni, Herodia Taku; Rama, Yohanes; Ndasi, Lucia De Costa; Najumetan, Tania; Senda, Siprianus S.; Manhitu, Joni (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Every religious person has certain basic principles in living life according to the teachings of their religion. For Catholic Christian believers, the basic principles of life are the teachings of Christ himself. Living the teachings of Jesus is an ideal Christian way of life. So the spirituality of Jesus Christ becomes the basic principle of Christian life. The text Philippians 2:1-11 talks about Jesus Christ and His primacy which is reflected by Paul. This research is intended to explore understanding of the spirituality of Jesus Christ in this text as a life guide for Christian believers. The method used is a library research method with a descriptive analysis approach. The study of the text Philippians 2:1-11 is carried out from the perspective of the spirituality of Jesus Christ as the basic principle of Christian life. The results of this research inspire Christian believers to always live the spirituality of Jesus Christ in their daily lives, especially servant spirituality which has the dimension of humility.